VARIABILITY OF ANATOMICAL FEATURES OF VEGETATIVE AND GENERATIVE ORGANS OF NITRARIA SCHOBERI L. IN SULAK POPULATION OF DAGHESTAN - Zagirbeg M. Аsadulaev; Magomed G. Gadzhiataev; Zulfira R. Ramazanova (Юг России: экология, развитие, 2018)
Aim. The work is devoted to the study of intrapopulation variability of the Sulak population of Nitraria schoberi L. Methods. The materials for this article were samples of vegetative and generative organs (shoot, leaf, fruit, seed) collected in 2015 in the natural population of N. schoberi in the Caspian lowland to the north-west of the village of Sulak. Results. The studied individuals of N. schoberi differ both in absolute indices of characteristics and in the degree of their variability, which is related both to micro growth conditions and to their genetic and age specific features. The prevalence of shrubs with a smaller diameter we associate with the relative youth of the population. In the semi-arid conditions of the Caspian lowland of Dagestan, N. schoberi bushes play a big role in the sand consolidation process, forming dunes and barrows, which is related to their ability to grow in diameter forming the beds during the rooting of lodging boughs. Conclusion. On the basis of discriminative analysis on the set of the characteristics of the leaf, the maximum self-identity of the 8th bush (80%) was determined, and the 5th bush (100%), on the basis of the fruit and seed, as confirmed by the Mahalanobis distances. The evaluation of signs of vegetative organs according to the results of dispersion analysis showed that the influence of the conditions of the year (h2 – 20,8%) is higher than the influence of the characteristics of the bushes themselves (h2 – 3,8%). Of generative characters, the greatest contribution is made by the length of the seed (h2 – 63,6).